Influencing early childhood education : key figures, philosophies and ideas - Pound, Linda, 1944- (McGraw-Hill, Open University Press, 2011)
"Thinking about early childhood education will offer an academic and critical approach to the wealth of theories that underpin elements of current practice in early childhood care and education. It will focus on analyzing the rise and interconnectedness of theories of learning and development."-- Resumé vydavatele
Keywords: předškolní výchova; filozofie výchovy; preschool education; philosophy of education; monografie; elektronické knihy; monographs; electronic books